2021
DOI: 10.1007/s12011-021-02744-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mercury Concentration in Honey from the Point of View of Human Body Exposure

Abstract: Honey is a highly valued product due to its nutritional value, pro-health and healing properties. Pollutants from the environment penetrate into nectar, honeydew, pollen and next into bee products and can cause human exposure after ingestion. Mercury (Hg) is a toxic metal to living organisms. This is why it was important to determine the level of Hg in consumed honey.The aim of this manuscript is to analyse mercury concentration in honeys collected on the territory of Poland. A total of 108 samples of honey pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…This trend was observed by another Polish recent study carried out by Brodziak−Dopierała et al (2021) [ 47 ], which discovered the highest content of Hg in honeydew (1.02 ± 0.49 μg kg −1 ). In both studies, the results associated with monofloral honey were wide−ranging depending on botanical origin, whereas reported average concentrations in multifloral honey of 0.54 ± 0.53 [ 45 ] and 0.31 ± 0.21 μg kg −1 [ 47 ], were slightly higher but consistent with our results (0.2 ± 0.1 μg kg −1 ). In honey from Central Europe, a higher concentration of Hg has been found compared to our samples, up to 315 μg kg −1 in Croatia [ 48 ] and 212 μg kg −1 in a contaminated site in Slovakia [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This trend was observed by another Polish recent study carried out by Brodziak−Dopierała et al (2021) [ 47 ], which discovered the highest content of Hg in honeydew (1.02 ± 0.49 μg kg −1 ). In both studies, the results associated with monofloral honey were wide−ranging depending on botanical origin, whereas reported average concentrations in multifloral honey of 0.54 ± 0.53 [ 45 ] and 0.31 ± 0.21 μg kg −1 [ 47 ], were slightly higher but consistent with our results (0.2 ± 0.1 μg kg −1 ). In honey from Central Europe, a higher concentration of Hg has been found compared to our samples, up to 315 μg kg −1 in Croatia [ 48 ] and 212 μg kg −1 in a contaminated site in Slovakia [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Hg content in Italian honey has been investigated also by Quinto et al (2016) [ 33 ], who recorded a mean concentration of 0.19 ± 0.17 μg kg −1 , confirming our results. In a recent research conducted by Fischer et al (2022) [ 45 ] in honey from Poland, the highest Hg concentration was found in honeydew (0.72 ± 0.46 μg kg −1 ), with a result similar to ours (0.6 ± 0.3 μg kg −1 ), and for honey of other botanical origins the level was always below 0.5 μg kg −1 , as in this study (except for ailanthus, slightly higher). This trend was observed by another Polish recent study carried out by Brodziak−Dopierała et al (2021) [ 47 ], which discovered the highest content of Hg in honeydew (1.02 ± 0.49 μg kg −1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…THg concentrations in our samples are all below WHO standards (Joint FAO/WHO Expert Committee, 2011). Compared with previous THg concentrations in bees and bee products, it is unlikely that beekeeping products from North American honey bees pose a risk of Hg to human health (Astolfi et al, 2021;Fischer et al, 2021).…”
Section: Resultsmentioning
confidence: 92%
“…These authors reported increased As and Hg levels in summer honey samples when compared with winter stores and concluded that heavy metal levels in honey differed significantly by season. Additionally, Fischer et al (2022) and Winiarska‐Mieczan et al (2021) reported statistically higher Hg and Pb concentrations, respectively, in multicomponent honeys when compared with single‐component samples. During the summer months, more plants bloom (Zarić et al 2016), thus more honeybees visit more vegetation types to collect pollen and nectar, suggesting that summer honey sources are more multicomponent and more exposed to environmental pollutants when compared with winter honey.…”
Section: Discussionmentioning
confidence: 97%